1980
DOI: 10.2136/sssaj1980.03615995004400030015x
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Tagged Nitrogen Fertilizer Applied to Irrigated Corn

Abstract: A field experiment was conducted for 2 years with ammonium sulfate tagged with 5.93 atom % 15N to determine the fate of N fertilizer applied to sprinkler‐irrigated corn (Zea mays L.). All areas of triplicate, 356‐cm square plots were treated with 50 or 150 kg tagged N/ha. N fertilizer used by the crop and that remaining in the top 240 cm of soil were measured. NH4+‐N and NO3‐‐N in the 0‐ to 10‐cm layers after the second harvest also were determined. Grain yields in 1976 did not differ significantly. In 1977 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
33
2
6

Year Published

1990
1990
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 0 publications
11
33
2
6
Order By: Relevance
“…Nitrogen use efficiency for maize in the United States has increased more than 30% over the last 20 yr (Fixen and West, 2002). Early 15 N work with maize showed that 24.1 and 26.4% of the applied N was accounted for in the grain at N rates of 50 and 150 kg N ha -1 , respectively (Olson, 1980). Similar studies by Wienhold et al (1995) reported that maize grain use of N applied averaged 35%.…”
Section: Review and Interpretationmentioning
confidence: 98%
See 1 more Smart Citation
“…Nitrogen use efficiency for maize in the United States has increased more than 30% over the last 20 yr (Fixen and West, 2002). Early 15 N work with maize showed that 24.1 and 26.4% of the applied N was accounted for in the grain at N rates of 50 and 150 kg N ha -1 , respectively (Olson, 1980). Similar studies by Wienhold et al (1995) reported that maize grain use of N applied averaged 35%.…”
Section: Review and Interpretationmentioning
confidence: 98%
“…Using a fixed NUE for these trials when combining over locations and years would likely compress the variability in optimum N rates reported. Other estimates of NUE exist and are in the 30 to 40% range (Cassman et al, 2002;Olson, 1980;Olson and Swallow, 1984). Also, computing NUE by individual site was not possible because grain N concentrations were only reported in a few of the papers included in this work.…”
Section: ( )mentioning
confidence: 99%
“…Comme la dose 180 dépasse le besoin de la plante en azote, l'engrais azoté est utilisé moins efficacement dans ce cas. Legg et al (1979), Olson (1980), Kitur et al (1984), Liang et MacKenzie (1994a), ont aussi observé que les coefficients d'utilisation de l'engrais azoté tendent à diminuer avec les doses d'engrais.…”
Section: Conditions Climatiques Des Sitesunclassified
“…Olson (1980) a trouvé après deux ans de culture du maïs des valeurs moyennes de CUR plus élevées pour la dose 50 kg N ha -1 en comparaison à 150 kg N ha -1 . Une diminution significative de CUR a été observée par Liang et MacKenzie (1994a) quand la dose d'azote augmente de 170 à 400 kg ha -1 .…”
unclassified
“…These values are based mostly on research with 15 N tagged fertilizer where recoveries of N in corn grain ranges from 13 to 45%, and the amount not recovered in the soilplant system ranges from 23 to 64% (Olson, 1980;Kitur et al, 1984;Sanchez and Blackmer, 1988;Varvel and Peterson, 1990). There is much concern about unrecovered N fertilizer percentages that range from 23 to 64%, which is 40 to 108 kg N ha -1 if a rate of 168 kg N ha -1 is applied, because N that is not recovered in the root zone can lead to water and air pollution.…”
mentioning
confidence: 99%